Effects of dietary chlorogenic acid on cecal microbiota and metabolites in broilers during lipopolysaccharide-induced immune stress - Hu, Xiaodi; Zhen, Wenrui; Bai, Dongying; Zhong, Jiale; Zhang, Ruilin; Zhang, Haojie; Zhang, Yi; Ito, Koichi; Zhang, Bingkun; Ma, Yanbo (Frontiers in Microbiology, 2024)
The aim of this study was to investigate the effects of chlorogenic acid (CGA) on the intestinal microorganisms and metabolites in broilers during lipopolysaccharide (LPS) -induced immune stress.A total of 312 one-day-old Arbor Acres (AA) broilers were randomly allocated to four groups with six replicates per group and 13 broilers per replicate: (1) MS group (injected with saline and fed the basal diet); (2) ML group (injected with 0.5 mg LPS/kg and fed the basal diet); (3) MA group (injected with 0.5 mg LPS/kg and fed the basal diet supplemented with 1000 mg/kg CGA); and (4) MB group (injected with saline and fed the basal diet supplemented with 1000 mg/kg CGA).The results showed that the abundance of beneficial bacteria such as Bacteroidetes in the MB group was significantly higher than that in MS group, while the abundance of pathogenic bacteria such as Streptococcaceae was significantly decreased in the MB group. The addition of CGA significantly inhibited the increase of the abundance of harmful bacteria such as Streptococcaceae, Proteobacteria and Pseudomonas caused by LPS stress. The population of butyric acid-producing bacteria such as Lachnospiraceae and Coprococcus and beneficial bacteria such as Coriobacteriaceae in the MA group increased significantly. Non-targeted metabonomic analysis showed that LPS stress significantly upregulated the 12-keto-tetrahydroleukotriene B4, riboflavin and mannitol. Indole-3-acetate, xanthurenic acid, L-formylkynurenine, pyrrole-2-carboxylic acid and L-glutamic acid were significantly down-regulated, indicating that LPS activated inflammation and oxidation in broilers, resulting in intestinal barrier damage. The addition of CGA to the diet of LPS-stimulated broilers significantly decreased 12-keto-tetrahydro-leukotriene B4 and leukotriene F4 in arachidonic acid metabolism and riboflavin and mannitol in ABC transporters, and significantly increased N-acetyl-Lglutamate 5-semialdehyde in the biosynthesis of amino acids and arginine, The presence of pyrrole-2carboxylic acid in D-amino acid metabolism and the cecal metabolites, indolelactic acid, xanthurenic acid and L-kynurenine, indicated that CGA could reduce the inflammatory response induced by immune stress, enhance intestinal barrier function, and boost antioxidant capacity.We conclude that CGA can have a beneficial effect on broilers by positively altering the balance of intestinal microorganisms and their metabolites to inhibit intestinal inflammation and barrier damage caused by immune stress.